The Use of Collaborative Problem Solving on Mathematical Representation in Solving One Variable Linear Equation Problem in Junior High School - Amelia, Lisa; Indaryanti (Department of Mathematics Education Program IPI Garut, 2023)
Penelitian ini bertujuan untuk melihat dan mendeskripsikan kemampuan representasi matematis siswa pada materi Persamaan Linier Satu Variabel (PLSV) setelah diterapkan model Collaborative Problem Solving (CPS). Metode penelitian yang digunakan adalah deskriptif dengan analisis data secara kuantitatif dan kualitatif sesuai dengan indikator representasi matematis. Penelitian ini dilaksanakan di SMP Negeri 6 Indralaya Utara di kelas VII.1 dengan melibatkan sebanyak 16 siswa sebagai subjeknya. Pengumpulan data dilakukan dengan memberikan tes tertulis berupa soal uraian dan hasil wawancara dengan siswa. Teknik analisis data yang digunakan meliputi memeriksa tes uraian merujuk pada indikator representasi matematis yaitu visual, simbolik dan verbal. Data yang telah terkumpul kemudian dianalisis berdasarkan pedoman penskoran yang merujuk pada indikator representasi matematis. Hasil analisis data selanjutnya dikelompokkan menjadi tiga kategori yaitu tinggi, sedang, dan rendah. Berdasarkan hasil analisis data didapatkan bahwa kemampuan representasi matematis siswa pada materi persamaan linier satu variabel setelah diterapkannya model CPS berada dikategori sedang dengan nilai rata-rata sebesar 59,687 dan skor rata-rata untuk indikator representasi visual yaitu sebesar 71,093, representasi simbolik 60,156, dan verbal 35,937. This study aimed to look at and describe students' mathematical representation abilities in the One Variable Linear Equation (PLSV) material after applying the Collaborative Problem Solving (CPS) model. The research method used was descriptive with quantitative and qualitative data analysis according to the indicators of mathematical representation. This research was conducted at SMP Negeri 6 Indralaya Utara in class VII.1 involving 16 students as participants. Data collection was carried out by giving written tests in the form of description questions and the results of interviews with students. The data analysis technique used included examining the description test referring to indicators of mathematical representation, namely visual, symbolic and verbal. The data were then analyzed based on scoring guidelines that refer to indicators of mathematical representation. The results of the data analysis were later categorized into three categories, namely high, medium, and low. Based on the results of data analysis, it was found that students' mathematical representation abilities in the material of one-variable linear equations after the implementation of the CPS model were in the moderate category with an average score of 59.687 and an average score for visual representation indicators that was 71.093, symbolic representation 60.156, and verbal 35.937.